Association of composite dietary antioxidant index with mortality in adults with hypertension: evidence from NHANES - Qin, Huali; Shen, Li; Xu, Danyan (Frontiers in Nutrition, 2024)
The objective of this study is to assess the correlation between composite dietary antioxidant index (CDAI) with all-cause mortality and cause-specific mortality in adults with hypertension.The cohort study comprised adult participants with hypertension from the NHANES database, spanning 9 cycles from 2001 to 2018. Follow-up was conducted until December 31, 2019. Multi-variable Cox regression analysis was utilized to ascertain hazard ratios (HR) and their corresponding 95% confidence intervals, evaluating the relationship between CDAI and the risks of all-cause and causespecific mortality. To further investigate the association between CDAI and mortality rates in adults with hypertension, Kaplan-Meier survival curves, restricted cubic splines (RCS), subgroup analyses and sensitivity analyses were employed.The analysis included 16,713 adults with hypertension (mean age 56.93 ± 0.23 years, 8,327[49.61%] male). During the mean follow-up time 102.11 ± 1.22 months, with 3908(18.08%) all-cause mortality occurred, 1082(4.84%) cardiovascular mortality and 833(3.80%) cancer mortality. Compared to the lowest quartile of CDAI, the weighted multivariate hazard ratios of participants in the highest quartile was 0.77(95% CI, 0.68-0.87) for all-cause mortality, 0.83(95% CI, 0.67-1.04) for cardiovascular mortality, and 0.64(95% CI, 0.50-0.82) for cancer mortality. RCS analysis demonstrated a nonlinear association of CDAI with all-cause and cancer mortality, and a linear association between CDAI and cardiovascular mortality. The results were robust in subgroup analyses and sensitivity analyses.Higher CDAI is associated with reduced all-cause mortality, cardiovascular mortality, and cancer mortality in hypertensive adults. Our findings highlight the importance of an antioxidant diet in improving outcomes in adults with hypertension.